Logical and Grammatical Relations in Word Categories: The Factor of Difference and Incarnation - Raupova, Laylo (International Journal of Psychosocial Rehabilitation, 2020)
Article links thought and language, logic, grammar bond linguistic and logical relations of mutual cooperation reflected, logic and linguistics link between thought and word, sentence, and that issues such as, in the category of logical thought and language description of its lexical and grammatical units problems such as articulation, which call both logic and linguists to the same level of research. Also in Europe from the sixteenth to the nineteenth centuries, logical linguistics - the dominance of linguistic direction, which equates logical and linguistic categories (phenomena), is a serious scientific step towards restricting logic and grammar are connected with such names as in philosophy F.Hegel, in linguistics V.Humbolt, our work is, basically, about the errors in grammatical analysis of grammatical categories and criteria. Logic works according to the content. Linguistic analysis (grammar) prefers the form rather the content and it is for the next period of the property for European science. The grammatical tradition of the Orient (including Arabic / Islam), which relied on the form factor, in the early stages of development was consistent in distinguishing logical and linguistic phenomena in descriptive linguistics (American structuralism). Logic was based on the content of the event , and grammar - on the basis of form . For example, grammatical descriptions, based on medieval Arabic and ancient Indian grammatical tradition, were usually small and compact, and generally consisted of a paradigm of forms (compact tables in Arabic, sutra - rule in India). Such chart is proved by the fact that both ancient Hindus and medieval Islamic linguists were so skilled at giving all the grammatical details, rules and exceptions in “bayt’”s.